2015
DOI: 10.1166/jbn.2015.2148
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake and Cytotoxic Effect of Epidermal Growth Factor Receptor Targeted and Plitidepsin Loaded Co-Polymeric Polymersomes on Colorectal Cancer Cell Lines

Abstract: Encapsulating chemotherapy drugs in targeted nanodelivery systems is one of the most promising approaches to tackle cancer disease, avoiding side effects of common treatment. In the last decade, several nanocarriers with different nature have been tested, but polypeptide-based copolymers have attracted considerable attention for their biocompatibility, controlled and slow biodegradability as well as their low toxicity. In this work, we synthesized, characterized and evaluated poly(trimethylene carbonate)-bock-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In search of alternatives, two nanoparticle-based formulations of plitidepsin have been tested in a renal xenograft tumor model,22 showing equivalent anticancer activity, compared to the Cremophor ® formulation, but improved biodistribution profiles, presenting novel tools for future plitidepsin-based therapies. Also, in colorectal cancer cell lines, the use of epidermal growth factor receptor (EGFR) targeted polymersomes greatly reduced plitidepsin cytotoxicity as well as the cellular uptake, indicating that the use of this targeted nanocarrier is a promising approach to tackle colorectal cancer disease and avoid the undesired effects of the usual treatment 23…”
Section: Designmentioning
confidence: 99%
“…In search of alternatives, two nanoparticle-based formulations of plitidepsin have been tested in a renal xenograft tumor model,22 showing equivalent anticancer activity, compared to the Cremophor ® formulation, but improved biodistribution profiles, presenting novel tools for future plitidepsin-based therapies. Also, in colorectal cancer cell lines, the use of epidermal growth factor receptor (EGFR) targeted polymersomes greatly reduced plitidepsin cytotoxicity as well as the cellular uptake, indicating that the use of this targeted nanocarrier is a promising approach to tackle colorectal cancer disease and avoid the undesired effects of the usual treatment 23…”
Section: Designmentioning
confidence: 99%
“…Goñi-de-Cerio et al [19] synthesized polypeptide-based copolymers such as poly (trimethylene carbonate)-bockpoly(L-glutamic acid) and encapsulated plitidepsin for targeting potential to EGFR with regard to HT29 and LS174T colorectal cancer cell lines. The cytotoxicity profile indicated excellent biocompatibility and cellular uptake of EGFR targeted and plitidepsin loaded polymersome indicated that colorectal cancer cell lines were more sensitive to anti-EGFRdrug-loaded than non-targeted drug-loaded polymersomes [19].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…A recent investigation demonstrated that plitidepsin exerts its antitumor activity by targeting eEF1A2 [49]. Nanoparticles with poly (trimethylene carbonate)-bockpoly(L-glutamic acid) derived polymersomes and plitidepsin were designed to target epidermal growth factor receptor (EGFR) and results have showed that the new designed composite exhibited significant antitumor activity against cancer cells overexpressing EGFR both in vitro and in vivo [50].…”
Section: Anticancer Peptides That Target the P38 Mapk Or Jnk Pathwaymentioning
confidence: 99%